THE WORLD NEEDS IN A UNIQUE THEORY OF DEVELOPMENT - Вelopolsky, Nickolay (Вісник Економіки, 2017)
Now, the mankind is in danger. It has found itself in this dangerous situation because there is no fundamental scientific theory of development and improvement of the social systems (production, economic, state systems and the world as a whole). This situation makes future existence of the mankind impossible. The aim of the paper is to show how to arrange the social systems both at present and in future. Unfortunately, there is no single integrated scientific discipline that studies the social systems comprehensively. It’s high time for all technical, social and natural sciences to concentrate their efforts on studying and arranging the social systems, finding their place, “niche" in this process.